Kesiapan Beltim dalam Menghadapi MEA - Triyono, Agus (FAKULTAS SYARIAH DAN EKONOMI ISLAM IAIN SYAIKH ABDURRAHMAN SIDDIK BANGKA BELITUNG, 2017)
On the investment side, the MEA creates a climate that supports the entry of Foreign Direct Investment (FDI) that can stimulate economic growth through technological development, employment field creation, human capital development and easier access to world markets. With the presence of this MEA event, Indonesia has an opportunity to take advantage of domestic economies of scale as a basis to gain profit. However, Indonesia still has many challenges and risks that will arise if the MEA has been fully implemented. East Belitung Regency as one of the areas that provide an advantage for the Province of Bangka Belitung Islands began to show the identity as a region ready to welcome MEA, but the question arises as to what challenges will be faced. The challenges faced by Beltim starting from the low utilization of human resources, the Beltim Government has not issued its own policies on employment and the increasing educated unemployment who are unable to be absorbed by the formal job market.